Antiangiogenic treatment approaches in breast cancer. (September 2013) - Bartsch, Rupert; Berghoff, Anna S; Preusser, Matthias; Steger, Guenther G; Zielinski, Christoph C
SUMMARY The term 'breast cancer', as it is understood today, comprises heterogeneous disease entities with major disparities in terms of underlying tumor biology, treatment options and outcome. Nonetheless, all breast cancer subtypes depend upon neovascularization for growth and metastatic spreading, indicating that antiangiogenic strategies may constitute a highly effective treatment approach. Currently, the only antiangiogenic agent approved for breast cancer treatment is bevacizumab, a humanized monoclonal antibody targeting VEGF-A. In combination with chemotherapy, bevacizumab improved outcomes in terms of progression-free survival and response rate in the first- and second-line palliative setting, while overall survival remained unchanged. This fact prompted the US FDA to withdraw their approval for bevacizumab in breast cancer, while approval was retained in Europe. Other antiangiogenic agents, such as sunitinib, sorafenib or aflibercept, were either of limited effectiveness in breast cancer or concerns were raised due to the high toxicity rates. In order to fully exploit the potential benefit of antiangiogenesis, the identification of reliable predictive markers is urgently warranted. This article reviews the data on antiangiogenic treatment approaches in breast cancer, with an emphasis on bevacizumab, and discusses potential future treatment options.